Surface Energy and Lewis Acid-base Characteristics of Lignocellulosic Fibers upon Modification by Chemical Vapor Deposition of Trichloromethylsilane: An Inverse Gas Chromatography Study - Gamelas, J. A. F. (2018)
J. A. F. Gamelas, M. Azpeitia, P. J. Ferreira & A. Tejado (2018) Surface Energy and Lewis Acid-base Characteristics of Lignocellulosic Fibers upon Modification by Chemical Vapor Deposition of Trichloromethylsilane: An Inverse Gas Chromatography Study, Journal of Wood Chemistry and Technology, 38:3, 264-275, DOI: 10.1080/02773813.2018.1454961